Retinal Contrast Gain Control and Temporal Modulation Sensitivity Across the Visual Field in Glaucoma at Photopic and Mesopic Light Conditions - João, Catarina A. R.; Scanferla, Lorenzo; Jansonius, Nomdo M. (Investigative ophthalmology & visual science, 2019)
Glaucoma affects many aspects of visual performance, including adaptation, and this may depend on ambient luminance. We determine the influence of glaucoma and luminance on temporal aspects of adaptation, specifically on contrast gain control and temporal modulation sensitivity (TMS). This case-control study included 12 glaucoma patients and 25 age-similar controls (50-70 years). Threshold perimetry was performed with a minimized testing grid (fovea and four peripheral locations). Stimuli (Goldmann size III 50 ms increment/decrement) were presented on a time-varying background with sinusoidally-modulated luminance (amplitude 60%; frequency 0-30 Hz; mean background luminance, 1 and 100 cd/m2). TMS (2.5-30 Hz) was measured in the same locations with a sinusoidally-modulated stimulus (Goldmann size IV, 334 ms) on a steady background (1 and 100 cd/m2). In healthy subjects, contrast sensitivity decreased with increasing background modulation frequency and increased again at very high frequencies, indicating contrast gain control. Minimum sensitivity was located between 2.5 and 20 Hz, depending on luminance and eccentricity. In glaucoma patients, the same frequency dependency was found (P = 0.12) but with an overall reduced sensitivity (P = 1 × 10-5), independent of luminance (P = 0.20). Decrements differentiated better between glaucoma and healthy subjects than increments (P = 0.004). TMS was reduced in glaucoma (P = 5 × 10-6) across all frequencies and luminance levels, with complete loss for high frequencies at 1 cd/m2. Contrast gain control is largely unaffected in glaucoma, suggesting intact amacrine cell function. Perimetry with decrements or a high-frequency stimulus on a low-luminance background seems best to differentiate between glaucoma and healthy subjects.